The Implementation of Online Learning for Economic Education Students at the University - Nanik Hindaryatiningsih; Hartina Hartina; Ramly Ramly; Edy Karno (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study was to determine and analyze the implementation of online learning on university students majoring in economic education at Halu Oleo University, Kendari. This type of research was a case study research. The informants in this study consisted of Economic Education students who were taken using the Purposive Sampling technique (n=100 students). The data were collected through questionnaires, interviews and documentation.  The data analysis used data reduction, data presentation, and conclusion. Test the validity of the data using triangulation techniques. The findings of this study were the implementation of online learning for Economic Education students was as follows: the learning applications most often used by Economic Education students were zoom meetings, WhatsApp groups and google classroom. Regarding the availability of learning time, students felt that it was enough, although it cannot be denied that sometimes it was also not enough. To access online learning, Economics Education students used a private packet connection type with less stable network quality. Economic education students' learning readiness was quite good, but the concentration and involvement of students were not good and the ability to understand learning materials is also still lacking.  This study concluded that online learning in university could be used a variation of device technology which was designed by a teacher or used from the internet.